Electronic structure and thermoelectric behavior of the new halide double perovskite Cs 2 RuGeCl 6 - Laranjeira, José A.S. [UNESP]; Azevedo, Sérgio A.; Albuquerque, Anderson R.; Cabral, Luis A. [UNESP]; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
Halide perovskites are well-known for their outstanding properties. They have driven suitable advances in materials science and technology, such as tunable band gap energies, broad light absorption spectrum, long carrier diffusion lengths, and low exciton binding energies. Therefore, this study presents a novel lead-free double halide perovskite Cs 2 RuGeCl 6 . This structure is both thermodynamically and mechanically stable, exhibiting a bulk modulus of ( K ) of 47.61 GPa, indicating a moderately incompressible structure. An indirect band gap of 2.06 eV was identified, and the band structure reveals three distinct bands near the top of the valence band. These bands serve as anti-trapping states, confining photogenerated holes and reducing the recombination rate. Additionally, the pristine Cs 2 RuGeCl 6 also shows its potential as a thermoelectric material, achieving a figure of merit ( Z T ) of 0.7. The properties and characteristics of Cs 2 RuGeCl 6 , presented here, offer a sustainable and efficient alternative to lead-based systems.